2016
DOI: 10.1186/s40608-016-0108-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity (Class I-III), gestational weight gain and maternal leptin levels during and after pregnancy: a prospective cohort study

Abstract: BackgroundMaternal obesity is accompanied by maternal and fetal complications during and after pregnancy. The risks seem to increase with degree of obesity. Leptin has been suggested to play a role in the development of obesity related complications. Whether maternal leptin levels differ between obese and morbidly obese women, during and after pregnancy, have to our knowledge not been previously described. Neither has the association between maternal leptin levels and gestational weight gain in obese women. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…A significant increase was found in the concentration of leptin during the last trimester of gestation, which could possibly owe itself to the mobilization of the sources of nutrients necessary for fetal growth, such as maternal adipose tissue [ 16 ]. In the present study, a leptin concentration above 20 ng/mL during the third trimester of gestation was related to a greater gestational weight gain, which coincides with a study by Lacroix et al [ 4 ] on a group of pregnant adults in Quebec, Canada, who also demonstrated an association between a higher leptin concentration and a greater gestational weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant increase was found in the concentration of leptin during the last trimester of gestation, which could possibly owe itself to the mobilization of the sources of nutrients necessary for fetal growth, such as maternal adipose tissue [ 16 ]. In the present study, a leptin concentration above 20 ng/mL during the third trimester of gestation was related to a greater gestational weight gain, which coincides with a study by Lacroix et al [ 4 ] on a group of pregnant adults in Quebec, Canada, who also demonstrated an association between a higher leptin concentration and a greater gestational weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, excessive maternal weight in adult women is related to an increase in the supply of energetic substrates in the mother–child dyad. However, it is unknown whether this mechanism is similar in pregnant adolescents, whose own personal growth and development has not yet come to an end and who in the majority of cases do not suffer from overweight or obesity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal weight women leptin levels increase during gestation, peak in late second or early third trimester, decrease towards the end of the pregnancy and decline drastically postpartum, suggesting an important role during gestation . Obese pregnant women seem to have increased leptin levels compared with normal weight women, and morbidly obese women have the highest leptin values . Leptin has been reported to depress human myometrial contractility in vitro and to maintain uterine quiescence by inducing myometrial proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, multiple risk factors including advanced maternal age, certain ethnicities, obesity and excessive gestational weight gain (GWG), low socio‐economic status, parity, multiple pregnancy, pre‐existing medical conditions and high‐risk behaviours such as smoking and alcohol consumption, vitamin or nutrient deficiencies and low physical activity increase the risk for pregnancy complications. Comparatively, a healthy lifestyle reduces the risk .…”
Section: Introductionmentioning
confidence: 99%